Frequency and Grading of Diabetic Retinopathy in Diabetic End Stage Renal Disease Patients - Muhammad Hammad Ayub, Nadeem Hafeez Butt, Samreen Jamal, Muhammad Hassaan Ali (Pakistan Journal of Ophthalmology, 2016)
Purpose: To find out the prevalence of diabetic retinopathy (DR) and its grades in diabetic end stage renal disease (ESRD) patients. Place and Duration of Study: The study was conducted in Department of Ophthalmology, Jinnah Hospital, Lahore from May 2015 to November 2015. Materials and Methods: Patients aged 35 – 75 years of either gender with ESRD caused solely by diabetes were included in the study. Retinal examination was done using 90D slit lamp bio microscopy and 20D lens with indirect ophthalmoscope. Presence or absence of DR and grades of retinopathy were documented in each case following ETDRS classification of diabetic retinopathy. Results: There were 100 subjects in the study: 55% males and 45% females. Mean age was 53.99 ± 11.88 years. Frequency of diabetic retinopathy in diabetic ESRD patients was recorded in 51.0% of the cases. Of the diabetic retinopathy patients, 68.63% had non-proliferative (NPDR) while 31.37% had proliferative diabetic retinopathy (PDR). Out of 35 cases with NPDR, 34.29% had mild, 40.0% had moderate and 5.71% had severe NPDR. Out of 16 cases with PDR, 68.75% had mild to moderate PDR while 31.25% had high risk PDR. Conclusion: Diabetic retinopathy is quite prevalent among diabetic end stage renal disease patients. Non-proliferative diabetic retinopathy is significantly higher than proliferative diabetic retinopathy in such cases. Key words: Diabetic end stage renal disease, diabetic retinopathy, frequency.